Peningkatan Kesadaran dan Partisipasi Masyarakat Melalui Program Rutin Sabtu Bersih di Kelurahan Tanjung Sari - Sonia Widia Sipahutar; Citra Fidella Nababan; Gita Sonya Sagala; Alex Tua Sihombing; Glorya Simanjuntak; Robinhot Sihombing (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This community service aims to increase public awareness and participation in maintaining environmental cleanliness through the routine Clean Saturday program in Tanjung Sari Village. This activity involves 6th semester students of the Christian Education Management Study Program of IAKN Tarutung who actively participate in cleaning the environment in various locations every week, as well as being involved in waste management at the New Normal Main Waste Bank. The methods used are direct participation and participatory observation, with a focus on cleanliness actions and community education. The results of the service show an increase in public awareness, the formation of environmental working groups, and changes in behavior that support the sustainability of the program. This service provides a real contribution to building a culture of clean and healthy living in the community and strengthening the role of students in community empowerment. Keywords: community service, Clean Saturday, community participation, waste bank, community empowerment.